2016
DOI: 10.1159/000442725
|View full text |Cite
|
Sign up to set email alerts
|

Protein Evolution of Human Milk

Abstract: Given the documented short- and long-term advantages of breastfeeding, human milk (HM) as a sole source of nutrition for the first few months of newborn life is considered a normative standard. Each macroconstituent of HM plays a crucial role in the growth and development of the baby. Lipids are largely responsible for providing more than 50% of the energy as well as providing essential fatty acids and minor lipids that are integral to all cell membranes. Carbohydrates can be broadly divided into lactose and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Collection rates between A and B showed to be different, but only due to the collection at day 3, where most samples were missed. This confirms that HM collection can be especially problematic during the first few days after birth, when its production is not abundant 31 . As a result, the greatest obstacle to collecting HM samples in the present cohort was represented by the difficulty in establishing milk supply, which underpinned nearly half of the missed samples (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…Collection rates between A and B showed to be different, but only due to the collection at day 3, where most samples were missed. This confirms that HM collection can be especially problematic during the first few days after birth, when its production is not abundant 31 . As a result, the greatest obstacle to collecting HM samples in the present cohort was represented by the difficulty in establishing milk supply, which underpinned nearly half of the missed samples (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…Milk for girls was associated with higher levels of protein and TAAs, whereas milk for boys showed a trend towards higher levels of free glutamine when evaluated over the first 3 months of lactation. Interestingly, Thakkar et al also demonstrated that the protein content in milk for girls was slightly higher than that in milk for boys in, at least, the first 60 days of lactation [ 41 ]. They, however, did not report significant differences, possibly due to them analyzing gender differences per time point measured, in contrast to our statistical method which includes the first 3 months of lactation simultaneously.…”
Section: Discussionmentioning
confidence: 99%